2007
DOI: 10.1016/j.autrev.2007.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Role of leukotriene B4 receptors in rheumatoid arthritis

Abstract: The purpose of this review is to summarize the role that murine models of arthritis are playing in the understanding of human rheumatoid arthritis and how leukotriene B 4 (LTB 4 ) is emerging as an important target in this field. Both the collagen-induced arthritis (CIA) model and the K/BxN serum transfer arthritis model have contributed to outline the potential mechanisms involved in inflammatory arthritis. Indeed, the CIA model has contributed to the development of effective anti-TNF and anti-IL-1β based tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 38 publications
3
29
0
1
Order By: Relevance
“…Rakonjac and coworkers reported that COTL1 up-regulates Ca 2+ -induced 5LO activity as a scaffold of 5LO in the absence of phosphatidylcholine by in vitro assays (Rakonjac et al, 2006). Mathis and co-workers demonstrated LTB 4 receptors play a critical role in the recruitment of leukocytes to the inflammatory sites in mouse model of RA (Mathis et al, 2007). Thus, our results suggest that up-regulation of COTL1 may affect the 5LO activity involved in LT biosynthesis, and mediate inflammation in RA.…”
Section: Discussionsupporting
confidence: 48%
“…Rakonjac and coworkers reported that COTL1 up-regulates Ca 2+ -induced 5LO activity as a scaffold of 5LO in the absence of phosphatidylcholine by in vitro assays (Rakonjac et al, 2006). Mathis and co-workers demonstrated LTB 4 receptors play a critical role in the recruitment of leukocytes to the inflammatory sites in mouse model of RA (Mathis et al, 2007). Thus, our results suggest that up-regulation of COTL1 may affect the 5LO activity involved in LT biosynthesis, and mediate inflammation in RA.…”
Section: Discussionsupporting
confidence: 48%
“…As such, LTB 4 plays crucial roles in inflammation and immune responses (Luster and Tager, 2004;Mathis et al, 2007). Two G protein-coupled receptors (GPCRs) for LTB 4 were originally cloned in our laboratory.…”
mentioning
confidence: 99%
“…Significant elevations of LTB 4 and LTC 4 from neutrophils are also present in animal models that mimic RA, suggesting that the 5-LOX pathway is significantly involved in generating inflammatory arthritis [148,149]. factors [152].…”
Section: Musculoskeletalmentioning
confidence: 99%
“…In patients with aspirin intolerance, nasal secretions contain increased levels of LTC 4 and LTD 4 histamine, and FLAP [55,56]. The incidence of aspirin-intolerant syndrome is about 10% of the US population, with most NSAIDs showing some level of cross-reactivity [57,58].…”
Section: Pulmonarymentioning
confidence: 99%
See 1 more Smart Citation